2020
DOI: 10.1002/jbmr.4108
|View full text |Cite
|
Sign up to set email alerts
|

Grade 1 Vertebral Fractures Identified by Densitometric Lateral Spine Imaging Predict Incident Major Osteoporotic Fracture Independently of Clinical Risk Factors and Bone Mineral Density in Older Women

Abstract: Because prevalent vertebral fracture (VF) is a strong predictor of future fractures, they are important to identify in clinical practice as osteoporosis medications are effective and can be used to reduce fracture risk in postmenopausal women with VF. Lateral spine imaging (LSI) with dual-energy X-ray absorptiometry (DXA) can be used to diagnose VFs accurately but is not widespread in clinical practice. The prognostic value of grade 1 (20% to 25% compression) VFs diagnosed by LSI with DXA has been insufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 43 publications
2
19
1
Order By: Relevance
“…Finally, the incidence of VF (6.6%) and the incidence rate (15.55 women/10 3 per year) that our group reported in 2019 were very similar to those depicted by Johansson et al (1) in their present study.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Finally, the incidence of VF (6.6%) and the incidence rate (15.55 women/10 3 per year) that our group reported in 2019 were very similar to those depicted by Johansson et al (1) in their present study.…”
supporting
confidence: 92%
“…We read with great interest the recent article by Johansson et al (1) about grade 1 vertebral fractures (VFs) identified by vertebral fracture assessment (VFA) and the prediction of incident fractures in older women. We discuss several aspects of their article.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Johansson et al. [ 35 ] reported that grade 1 OVFs were associated with incident major osteoporotic fracture after adjustment for clinical risk factors and bone mineral density. In one recent study of ours [ 30 ], of the total five women with baseline minimal OVF, three had osteopenia and two had osteoporosis, and their OVF progression or new incident OVF rate at year-14 follow-up was similar to the women with baseline apparent OVF.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of asymptomatic morphometric fractures of the spine, the grade of the fracture (mild, moderate or severe) most likely also correlates with risk of subsequent fracture [8]. This can be determined by vertebral fracture assessment (VFA), a function of most modern dual-energy X-ray absorptiometry (DXA) devices, or by conventional X-rays.…”
Section: Fragility Fracturesmentioning
confidence: 99%